A CMOS class-AB instrumentation amplifier for micropower applications - De Lima, Jader A. [UNESP]; Silva, Sidnei F. [UNESP] (My University, 1998)
A simple micropower CMOS instrumentation amplifier comprising a double-input Gm-stage and a low-distortion class-AB output stage is presented. The amplifier was designed according to micropower techniques to achieve high values of low-frequency differential-gain and common-mode rejection and integrated in a digital-oriented 0.7μm n-Well CMOS process. For a bias current of 130nA, amplifier standby power consumption is 26μW. Measurements revealed good characteristics at DC and low frequencies such as A dm=87dB and CMRR=-137dB. For a compensation capacitor of 4.5pF, it was found ΦM=73° and a unity-gain frequency of 47KHz. Offset voltage was below 0.7mV, typically. Resistive loads down to 10KΩ can be driven with a 1.3V peak-to-peak swing. Overall linearity is represented by a THD of - 42.9dB. Although bandwidth limitation occurs due to small bias currents, the proposed amplified can be advantageously employed in many control and low-frequency signal processing. © 1998 Editions Frontieres.